Relationship between Protein C and Antithrombin Levels with SOFA Score in Sepsis - Nurma Sheila; Adi Koesoema Aman; Achsanuddin Hanafie (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Sepsis is a life-threatening organ dysfunction caused by the failure of the host's response against infection. Organdysfunction in sepsis can be represented by an acute change in the SOFA score > 2 points as a consequence of infection.Proinflammatory cytokines in sepsis activate the coagulation cascade and cause a decrease in protein C and antithrombin III.This study aimed to determine protein C and antithrombin III levels in sepsis patients and their relationship with SOFA score.This study was an analytical study with a prospective cohort design. The subjects of this study were sepsis patients at AdamMalik General Hospital, Medan. Protein C, antithrombin III, and SOFA score were tested twice (first day and third day), andthe relationship between protein C and antithrombin III with SOFA score was analyzed. From 33 samples, it was found thatprotein C and antithrombin III levels were lower in sepsis patients. There was a significant negative correlation betweenprotein C and SOFA score on the first day (r= -0.502, p= 0.003), but no significant correlation was found on the third day.There was a significant negative correlation between antithrombin III and SOFA score on the first day (r= -0.513, p=0.002),but no significant correlation was found on the third day. It was concluded that there was a significant relationship betweenprotein C and antithrombin III with SOFA score on the first day of sepsis patients.